Birokrasi dan Struktur Kekuasaan dalam Organisasi Pendidikan Modern: dengan Pendekatan Max Weber - Indra Devi; Silfia Hanani; Iswantir M; Aisyah Syafitri; Nur Indri Yani Harahap (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This research examines the role of bureaucracy and power structure in modern educational organizations using the Max Weber's theoretical approach. The primary objective of this study is to understand how Weber's concepts related to bureaucracy and power can be applied in the context of contemporary educational institutions. The research methodology employed in this study is a literature review, involving a comprehensive examination of literature from various sources, including books, scholarly journals, and conference papers, relevant to Max Weber's theory, bureaucracy, and power structure in modern educational organizations. The collected data were qualitatively analyzed to support the research findings. The research findings indicate that Weber's bureaucratic principles, such as division of labor, hierarchy, and rational rules, still hold relevance in modern educational organizations. However, their impact may differ in an educational context, where aspects such as flexibility, innovation, and participation also hold significance. Furthermore, the power structure in modern educational organizations can be understood through Weber's concepts of authority and control. This study provides in-depth insights into how Weber's theory can help us comprehend the dynamics of bureaucracy and power in educational institutions, which, in turn, can support improvements and developments in modern education systems.